The dose response principle from philosophy to modern toxicology: The impact of ancient philosophy and medicine in modern toxicology science - Tsatsakis AM; Vassilopoulou L; Kovatsi L; Tsitsimpikou C; Karamanou M; Leon G; Liesivuori J; Hayes AW; Spandidos DA (ELSEVIER SCIENCE BV, 2022)
Since ancient times the concept of dose response, from a toxicological perspective, has been a matter of concern. Already by the 8th century BC and over the years, many enlightened people have attempted to interpret this phenomenon, observing and coming across its results and practical implementation through exposure to chemical substances, either from natural or synthetic sources. Nowadays, the environmental exposure of human populations to chemicals in terms of quantity and quality might differ. Nevertheless, dose response still remains an issue joining hands with scientific and technological progress. The aim of the present review is not only to briefly recount the history of the dose response concept, from ancient time theories to novel approaches, but also to draw the outline of challenges and requirements toxicology science needs to fulfill.